The Value of Assessing Higher Education Student Learning Outcomes - Tatiana Melguizo; Hamish Coates (SAGE Publishing, 2017)
Improving higher education student learning plays a critical role in advancing human capital. Assessment lies at the heart of such improvement, underlining the need for research and innovation in this field. This article reviews an AERA Open Special Topic published to advance assessment research and hence the success of higher education. It sketches key contexts, surveys selected articles, and stands back to frame future steps ahead.